From a backup technology to a strategy-outlining approach: the success story of cryopreservation. (March 2013) - Vajta, Gábor; Reichart, Anikó; Ubaldi, Filippo; Rienzi, Laura
During the past decade, cryopreservation of oocytes and embryos has become one of the most exciting areas in human-assisted reproduction. Improvement of the old techniques and introduction of alternative procedures have radically increased the overall efficiency and extended applicability. In parallel, the development of other laboratory techniques (embryo culture and preimplantation diagnostics) as well as medical, social, legal and cultural demands required the rapid and widespread exploitation of the new possibilities. This review summarizes the main features of the technical development, including both achievements and controversies, and outlines the emerging assisted reproductive technique strategies based partially or predominantly on cryopreservation. Application of these new achievements may substantially modify our approach in many fields and increase the overall efficiency of infertility or fertility preservation treatments.